Higher rates of food insecurity and stress experienced by food systems workers during the first year of the COVID-19 pandemic - Spence, Emma H.; Niles, Meredith T.; Bertmann, Farryl; Mares, Teresa; Belarmino, Emily H. (Frontiers in Nutrition, 2024)
The present study examined the prevalence of food insecurity and perceived stress among food system workers relative to other members of the population during the first year of the COVID-19 pandemic. It also explored perspectives on the role of food system workers during the pandemic and their experiences working during this time. Data were collected via an online survey in spring 2021. The sample was comprised of 441 residents of Vermont, United States, including 41 food system workers. Regression models identified higher rates of food insecurity and perceived stress among food system workers during the first year of the pandemic. However, these relationships were not maintained when the models were adjusted for income and job disruption, suggesting that the associations were primarily due to the economic vulnerability of food system workers. Most respondents indicated concern for the health and well-being of food system workers, felt that food system workers were undervalued, and agreed that the well-being of food system workers should be prioritized. However, opinions were split regarding whether it was worth the health risk to require farms and food processing plants to stay open to maintain the food supply. Half of food system workers believed that their work had compromised their well-being during the pandemic, although several also identified their jobs as pathways for accessing food. The findings provide valuable information for decision-makers seeking to increase the resilience of the food supply and the food system workforce.